Affecting Factors of Teenage Sexual Lifestyle and Its Implications for Transmission of HIV/AIDS in Jayapura District - Sherly Novita Mamoribo (Health Notions, 2019)
Sexual lifestyle in present days has become a social perspective, which deals with marriage and sexual relationships, as well as adolescent moral decadence, cohabiting, liquor, and intercourse by which no rules above them. This research aimed to find out factors that affected adolescent sexual lifestyle and its implication on HIV/AIDS transmission in Jayapura District. Using an explanatory research method, this research, which took place on October 2012, applied a cross-sectional approach with 280 adolescences from three Jayapura-based colleges as study samples, which were collected by a simple random sampling and measured by a pre-tested structured questioner. Results obtained from descriptive analysis reported risky sexual lifestyle (51.4%), poor knowledge of sexually transmitted disease and condom (67.9%), permissive response to sexuality (62.9%), and peers permissive response to sexuality (63.2%). Factors that correlated to the adolescent sexual lifestyle included knowledge (p-value = 0.000), attitude (p-value = 0.001), leisure time activities (p-value = 0.000), parental attitude (p-value = 0.000), peer attitude (p-value = 0.000), and residency status (p-value = 0.000). Furthermore, the most significant effect on the adolescent sexual lifestyle proved to be peer attitude (p-value = 0.000) and OR = 6.540, which meant that the peer permissive response had a possible effect of 6.540 higher than the non-permissive response. Keywords: HIV/AIDS; sexual lifestyle; adolescent; transmission